Combined mineral-supplemented diet and exercise increases bone mass and strength after eight weeks and maintains increases after eight weeks detraining in adult mice - Friedman, Michael A.; Szczepankiewicz, Robert P.; Kohn, David H. (PLOS ONE, 2018)
Exercise has long-lasting benefits to bone mass and structural strength even after cessation. Combining exercise with a calcium- and phosphorus-supplemented diet increases cortical bone mineral content (BMC), area, and yield force more than exercise alone in adult mice. These increases could also be maintained after stopping exercise if the modified diet is maintained. It was hypothesized that combining exercise with a mineral-supplemented diet would lead to greater cortical BMC, area, and yield force immediately after a lengthy exercise program and after an equally long period of non-exercise (detraining) in adult mice. Male, 16-week old C57Bl/6 mice were assigned to 9 weight-matched groups–a baseline group, exercise and non-exercise groups fed a control or mineral-supplemented diet for 8 weeks, exercise + detraining and non-exercise groups fed a control or mineral-supplemented diet for 16 weeks. Exercise + detraining consisted of 8 weeks of exercise followed by 8 weeks without exercise. The daily exercise program consisted of running on a treadmill at 12 m/min, 30 min/day. After 8 weeks, mice fed the supplemented diet had greater tibial cortical BMC and area, trabecular bone volume/tissue volume (BV/TV), bone mineral density (vBMD), yield force, and ultimate force than mice fed the control diet. Exercise increased cortical BMC and area only when coupled with the supplemented diet. After 16 weeks, both exercised and non-exercised mice fed the supplemented diet maintained greater tibial cortical BMC and area, trabecular BV/TV, vBMD, yield force, and ultimate force than mice fed the control diet. Combining exercise with a mineral-supplemented diet leads to greater bone mass and structural strength than exercise alone. These benefits remain after an equally long period of detraining. Long-term use of dietary mineral supplements may help increase and maintain bone mass with aging in adult mice.